Long-Term Beta-Blocker Therapy After Myocardial Infarction Without Heart Failure in the Reperfusion Era—Systemic Review and Meta-analysis. Issue 5 (May 2022) - Kim, Youngju; Byun, Sungwook; Kim, Hee-Yeol; Kim, Dong-Bin
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Beta-blockers are recommended as a standard treatment for patients who experience a myocardial infarction (MI). However, the evidence supporting this recommendation is based on the prereperfusion era data. This review aims to evaluate the effectiveness of long-term (≥1 year) beta-blocker therapy in post-MI patients without clinical heart failure (HF) in the reperfusion era. We included observational cohort studies, which compared at least 1 year use of beta-blockers to no beta-blockers in patients with an acute MI, but without HF. The clinical endpoint considered was all-cause mortality, except for cardiovascular death in one study. Five cohort studies and 217, 532 patients were included. One study demonstrated a reduction in all-cause mortality with beta-blockers, whereas, in 4 studies, there was no difference in the death rate. The pooled estimate by random effect showed that beta-blocker treatment does not reduce mortality (odds ratio 0.800, 95% confidence interval 0.559–1.145) with high heterogeneity (I2 = 94%). This meta-analysis shows that the use of oral beta-blockers for 1 year or more does not reduce the mortality of MI patients without HF. Large randomized trials need to evaluate beta-blocker discontinuation after an acute MI.